Asthma, inhaled corticosteroid treatment, and growth. Issue 6 (June 1992) - Ninan, T K; Russell, G
Abstract : To evaluate the effects on growth of inhaled corticosteroid treatment (ICT) and of the quality of control of asthma, height velocity was studied in 58 prepubertal children attending a specialist asthma clinic because of chronic asthma that was difficult to control. The height velocity standard deviation (SD) score was maximal when the asthma was well controlled both before (0.01) and after (-0.07) starting ICT. It was least when the asthma was poorly controlled both before (-1.50) and after (-1.55) starting ICT. The effectiveness of control correlated significantly with the height velocity SD score, both before and after ICT was started. No evidence was found that the administration of ICT has an adverse effect on growth.